Modulation of Intestinal Inflammation by Minimal Enteral Nutrition With Amniotic Fluid in Preterm Pigs. (28th May 2013) - Østergaard, Mette V.; Bering, Stine B.; Jensen, Michael L.; Thymann, Thomas; Purup, Stig; Diness, Marie; Schmidt, Mette; Sangild, Per T.
Abstract : Background : Necrotizing enterocolitis (NEC) is a severe inflammatory disorder, associated with the difficult transition from parenteral to enteral feeding after preterm birth. We hypothesized that minimal enteral nutrition (MEN) with amniotic fluid (AF), prior to enteral formula feeding, would improve resistance to NEC in preterm pigs. Methods : Experiment 1: IEC‐6 cells were incubated with porcine (pAF) and human AF (hAF) to test AF‐stimulated enterocyte proliferation and migration in vitro. Experiment 2: Cesarean‐delivered, preterm pigs were fed parenteral nutrition and MEN with pAF, hAF, or control fluid (MEN‐pAF, MEN‐hAF, or MEN‐CTRL; all n = 9) for 2 days before tissue collection. Experiment 3: Preterm pigs were fed MEN diets as in experiment 2, but followed by 2 days of enteral formula feeding, which predisposes to NEC (NEC‐pAF, NEC‐hAF, or NEC‐CTRL; n = 10–12). Results : Both pAF and hAF stimulated enterocyte proliferation and migration in vitro. In experiment 2, MEN‐pAF and MEN‐hAF pigs showed increased body weight gain and reduced intestinal interleukin (IL)–8 and colonic IL‐6 levels, indicating reduced inflammatory response. In experiment 3, body weight gain was highest in the 2 groups fed AF as MEN, but NEC incidences were similar (NEC‐pAF) or increased (NEC‐hAF) compared with controls. Conclusions : Intake of pAF or hAF improved body growth and modulated intestinal inflammatory cytokines during a period of parenteral nutrition, but did not protect against later formula‐induced NEC in preterm pigs. Further studies are required to show if MEN feeding with species‐specific AF, combined with an optimal enteral diet (eg, human milk), will improve adaptation during the transition from parenteral to enteral feeding in preterm neonates.